THE PROBLEM-SOLVING ANALYSIS IN SOLVING TRIGONOMETRIC PROBLEMS BASED ON BRANSFORD & STEIN STEP OF CAMPERS STUDENTS - Fortuneladewi, Asri (Kadikma, 2022)
This research aims to describe how the problem-solving ability of campers students in solving trigonometry problems. This study uses the problem-solving theory by Bransford & Stein that consists of five steps, namely identifying problems, defining goals, exploring possible strategies, anticipating results and acting, and looking back and learning. The technique of taking the subject in this study used purposive sampling. The research subjects were five students of IPA vocational high school. The instruments used were tests, interviews, and questionnaires. The results showed that campers students in solving trigonometry problems are pretty good. The students can fulfill four indicators of Bransford & Stein's problem-solving: (1) collect information, (2) define goals, (3) find problem-solving strategies, (4) use the correct arithmetic operations, and can find the result.